Consistent democracy. The elective franchise for women. Twenty-five testimonies of prominent men, viz: ex-Gov. Anthony of R.I., Rev. Henry Ward Beecher, Rev. Wm.H. Channing [etc.] - Stone, Lucy, 1818-1893; Susan B. Anthony Collection (Library of Congress); National American Woman Suffrage Association Collection (Library of Congress) (Worcester, T.W. Higginson; Boston, R.F. Wallcut; [etc., etc.], 1858)
These are very brief (paragraph-length) statements of support for woman suffrage. Among the "prominent men" included are Henry Ward Beecher, William Lloyd Garrison, Horace Greeley, Thomas Wentworth Higginson, Samuel J. May, Theodore Parker, Wendell Phillips, Gerrit Smith, William H. Channing, the Ohio Senate, and the Wisconsin legislature.
Also available in digital form on the Library of Congress Web site.
LC copy no. 11 in a collection of pamphlets lettered: Miscellaneous speeches, etc.
Keywords: Women -- Suffrage